2011
DOI: 10.4304/jltr.2.3.688-696
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Reading Comprehension: The Effect of Adding a Dynamic Assessment Component on EFL Reading Comprehension

Abstract: Abstract-Dynamic assessment (DA) stresses the need for unifying assessment and instruction. This paper presents an interactionist model of DA to assessment in reading comprehension of 30 Iranian male students who were selected based on available sampling procedure. Data collection procedures before and after implementation of DA were done through administration of multiple-choice reading comprehension test. The results of students' performance before and after implementation of DA were calculated through t-tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…The reasoning and justification presented in the preceding paragraph could provide a cogent reason why DA has been shown to be beneficial in the improvement of language skills and subskills like speaking (Ahmadi- Safa et al, 2015), reading (Mardani & Tavakoli, 2011), and vocabulary learning (Hessamy & Ghaderi, 2014), and pronunciation rhythm in the present study.…”
Section: Addressing the First Hypothesismentioning
confidence: 65%
See 1 more Smart Citation
“…The reasoning and justification presented in the preceding paragraph could provide a cogent reason why DA has been shown to be beneficial in the improvement of language skills and subskills like speaking (Ahmadi- Safa et al, 2015), reading (Mardani & Tavakoli, 2011), and vocabulary learning (Hessamy & Ghaderi, 2014), and pronunciation rhythm in the present study.…”
Section: Addressing the First Hypothesismentioning
confidence: 65%
“…In the same vein, Mardani and Tavakoli (2011) investigated the role of dynamic assessment in reading comprehension of 30 Iranian male learners. During the mediation phase the researchers followed an interactionist method which was based on cooperative dialog.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In assessing the effect of dynamic assessment accompanied by technology in our country, Birjandi and Ebadi (2012) carried out a web-based qualitative inquiry in the synchronous computer-mediated communication (SCMC) via Web 2.0. Mardani and Tavakoli (2011) used an interactionist approach in the sandwich format to group dynamic assessment to study the effect of adding a dynamic assessment to EFL reading comprehension. Sadeghi and Khanahmadi (2011) conducted a research on 60 Iranian male and female intermediate EFL learners to assess the viability of dynamic assessment used as an instructional adjunct in the development of Iranian EFL learners' grammar.…”
Section: Review Of Literaturementioning
confidence: 99%
“…As for reading, the comparison study of Mardani and Tavakoli (2011) showed the positive effects of DA while Ajideh, Farrokhi and Nourdad (2012) found that learners with different levels of language proficiency might obtain different benefits from DA procedure. But the two studies only centered on the results rather than the processes of DA.…”
Section: Reading and Listeningmentioning
confidence: 95%